NEW LifeStyle: A Downloadable Teaching and Learning Program for Nutrition, Exercise, and Weight Management - David P. Miller; Sonia J. Crandall; Stephen Davis; Edward Ip; Gregg Jamback; Cynthia Burns; Donna Kronner; Gail Marion; John G. Spangler; Karen Vaden; JoAnne Vernon; Mara Z. Vitolins (Association of American Medical Colleges, 2012)
Abstract Introduction NEW (Nutrition, Exercise, and Weight Management) LifeStyle is a web-based teaching and learning program designed by the Department of Family and Community Medicine at Wake Forest School of Medicine to help students, educators, and the public learn about weight management issues as they relate to health and to the compassionate delivery of health care. Methods Modules play as PowerPoint presentations and include text, audio narration, figures, graphics, animations, and video. Each module has an associated pre- and postquiz to enhance learning. Each module takes between 10-15 minutes to complete. The modules can be completed in any order as each module is a stand-alone educational activity. All eight modules have been successfully implemented and evaluated among medical students in all four years at Wake Forest. Results The program development team conducted an evaluation study to determine effectiveness of the modules from a knowledge acquisition perspective. The Class of 2012 received all modules, with the Classes of 2013 and 2014 receiving 4 and 3, respectively. Response rates varied by class ranging from 22% for one module in the Class of 2012; up to 100% for two modules in the Class of 2012. Percent correct at posttest increased by up to 44% on retested items; up to 41% on new items; and up to 43% on the 10 total retested and new items (all p values < .009). Students scored lowest on the pretest for obesity bias (47%) and highest on the pretest for counseling (80%). Despite high pretest counseling scores, knowledge significantly increased at post-test (p = .009). Discussion Unique aspects of this program are its emphasis on confronting antiobesity bias among health care providers and training medical students in culturally sensitive weight management counseling. Materials within this program also draw attention to the connection of cancer to poor nutrition, physical inactivity, and excess weight-and how cancer risk can be lowered by making modifications to behavior.